Transition from Paper-Based Worksheets to Spreadsheets: An Exploratory Study of Opportunity to Learn in Linear Algebra Instruction - Nasrullah; Nurdin Arsyad; Alimuddin (Cita konsultindo, 2025)
This study explores the impact of transitioning from traditional paper-based worksheets to spreadsheet-based instruction on students' Opportunity to Learn (OTL) in a Linear Algebra course. Conducted with 37 undergraduate mathematics education students, the research employed a qualitative exploratory approach to examine changes in student engagement, conceptual understanding, and pedagogical awareness. The intervention began with procedural paper-based tasks and gradually introduced spreadsheet environments designed to foster conceptual exploration and mathematical argumentation. Data were collected through observations, student artifacts, and interviews, and analyzed using content analysis and learning trajectory comparison. The findings reveal that spreadsheet-based instruction enhanced computational accuracy, facilitated independent exploration, and promoted metacognitive engagement. A comparison between the hypothetical learning trajectory (HLT) and actual learning pathway (ALT) showed that students exceeded expectations, demonstrating improved conceptual reasoning and reflective thinking. The study concludes that spreadsheet integration—when embedded in argumentation-based learning—serves as a transformative pedagogical tool, expanding instructional quality and deepening students’ opportunity to learn in higher mathematics education.